School-based programmes for preventing smoking. - Thomas, R; McLellan, J; Perera, R (2013)
BACKGROUND: Helping young people to avoid starting smoking is a widely endorsed public health goal, and schools provide a route to communicate with nearly all young people. School-based interventions have been delivered for close to 40 years. OBJECTIVES: The primary aim of this review was to determine whether school smoking interventions prevent youth from starting smoking. Our secondary objective was to determine which interventions were most effective. This included evaluating the effects of theoretical approaches; additional booster sessions; programme deliverers; gender effects; and multifocal interventions versus those focused solely on smoking. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL), the Cochrane Tobacco Addiction Group's Specialised Register, MEDLINE, EMBASE, PsycINFO, ERIC, CINAHL, Health Star, and Dissertation Abstracts for terms relating to school-based smoking cessation programmes. In addition, we screened the bibliographies of articles and ran individual MEDLINE searches for 133 authors who had undertaken randomised controlled trials in this area. The most recent searches were conducted in October 2012. SELECTION CRITERIA: We selected randomised controlled trials (RCTs) where students, classes, schools, or school districts were randomised to intervention arm(s) versus a control group, and followed for at least six months. Participants had to be youth (aged 5 to 18). Interventions could be any curricula used in a school setting to deter tobacco use, and outcome measures could be never smoking, frequency of smoking, number of cigarettes smoked, or smoking indices. DATA COLLECTION AND ANALYSIS: Two reviewers independently assessed studies for inclusion, extracted data and assessed risk of bias. Based on the type of outcome, we placed studies into three groups for analysis: Pure Prevention cohorts (Group 1), Change in Smoking Behaviour over time (Group 2) and Point Prevalence of Smoking (Group 3). MAIN RESULTS: One hundred and thirty-four studies involving 428,293 participants met the inclusion criteria. Some studies provided data for more than one group.Pure Prevention cohorts (Group 1) included 49 studies (N = 142,447). Pooled results at follow-up at one year or less found no overall effect of intervention curricula versus control (odds ratio (OR) 0.94, 95% confidence interval (CI) 0.85 to 1.05). In a subgroup analysis, the combined social competence and social influences curricula (six RCTs) showed a statistically significant effect in preventing the onset of smoking (OR 0.49, 95% CI 0.28 to 0.87; seven arms); whereas significant effects were not detected in programmes involving information only (OR 0.12, 95% CI 0.00 to 14.87; one study), social influences only (OR 1.00, 95% CI 0.88 to 1.13; 25 studies), or multimodal interventions (OR 0.89, 95% CI 0.73 to 1.08; five studies). In contrast, pooled results at longest follow-up showed an overall significant effect favouring the intervention (OR 0.88, 95% CI 0.82 to 0.96). Subgroup analyses detected significant effects in programmes with social competence curricula (OR 0.52, 95% CI 0.30 to 0.88), and the combined social competence and social influences curricula (OR 0.50, 95% CI 0.28 to 0.87), but not in those programmes with information only, social influence only, and multimodal programmes.Change in Smoking Behaviour over time (Group 2) included 15 studies (N = 45,555). At one year or less there was a small but statistically significant effect favouring controls (standardised mean difference (SMD) 0.04, 95% CI 0.02 to 0.06). For follow-up longer than one year there was a statistically nonsignificant effect (SMD 0.02, 95% CI -0.00 to 0.02).Twenty-five studies reported data on the Point Prevalence of Smoking (Group 3), though heterogeneity in this group was too high for data to be pooled.We were unable to analyse data for 49 studies (N = 152,544).Subgroup analyses (Pure Prevention cohorts only) demonstrated that at longest follow-up for all curricula combined, there was a significant effect favouring adult presenters (OR 0.88, 95% CI 0.81 to 0.96). There were no differences between tobacco-only and multifocal interventions. For curricula with booster sessions there was a significant effect only for combined social competence and social influences interventions with follow-up of one year or less (OR 0.50, 95% CI 0.26 to 0.96) and at longest follow-up (OR 0.51, 95% CI 0.27 to 0.96). Limited data on gender differences suggested no overall effect, although one study found an effect of multimodal intervention at one year for male students. Sensitivity analyses for Pure Prevention cohorts and Change in Smoking Behaviour over time outcomes suggested that neither selection nor attrition bias affected the results. AUTHORS' CONCLUSIONS: Pure Prevention cohorts showed a significant effect at longest follow-up, with an average 12% reduction in starting smoking compared to the control groups. However, no overall effect was detected at one year or less. The combined social competence and social influences interventions showed a significant effect at one year and at longest follow-up. Studies that deployed a social influences programme showed no overall effect at any time point; multimodal interventions and those with an information-only approach were similarly ineffective.Studies reporting Change in Smoking Behaviour over time did not show an overall effect, but at an intervention level there were positive findings for social competence and combined social competence and social influences interventions.